MEMBACA GELIAT PENDIDIKAN DAN KEILMUAN DI SPANYOL ISLAM (TAHUN: 756-1494 M.) - Masruri, M. Hadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This paper is about to assert that the triumph of science in the Islamic Spain didn’t only occur in the period following the Umayyad dynasty II (c. 756-1031), but quite the dynasty during the reign of al-Muwahhidun (1078-1214) and reached its peak under the the reign of the Caliph Abu Yusuf Ya'qub al-Mansur (d. 580 h./1184 M). The intellectual glory of Andalusia marked several things: first, expedition scientists massively in the Umayyad II to the Eastern Islamic world in order to study and acquire as many references to the development of science upon his return to their Islamic Spain; Second, the migration of scientists to Eastern Andalusia happened in al-Muwahhidun dynasty is the transmission of knowledge from the East to the Islamic Spain; and the third, the translation movement in the 12th century and 13rd based in Toledo can be seen is the bridge to the current scientific knowledge of the Arab world to Europe, Islam is encouraged intellectual progress stretching in Andalusia. Keywords: Intellectual, Academic, Transmission of the expedition scientists.